"She wants me, she wants me not": Individual differences in attachment, rejection sensitivity, and self-esteem and men's perception of women's sexual interest. (October 2022) - Ruckel, Lindsay M.
Abstract: The present research builds on the meager but growing research on within-group differences in men's perception of women's sexual interest. Novel predictions rooted in Attachment theory (Bowlby, 1982) and the Rejection Sensitivity (RS) Model (Downey & Feldman, 1996) were tested in two cross-sectional studies. Heterosexual men (Study 1: N = 497, Study 2: N = 305) rated a series of behaviors on how much sexual interest they communicate had women engaged in them. In Study 2, they also reported how much sexual interest they perceived from women in a series of photographs. As hypothesized, men high in attachment anxiety perceived more sexual interest relative to their less anxious counterparts. Results were mixed for attachment avoidance, RS, and self-esteem. In Study 1, men high in avoidance and RS perceived less sexual interest, and self-esteem was positively associated with sexual interest perception. However, in Study 2, these hypotheses were unsupported. This research goes beyond gender differences and represents a step towards integrating related bodies of psychological literature for a better understanding of sexual interest perception. Results, implications, and future directions are discussed. Highlights: Addressed lack of research on within-group differences in men's sexual interest perception. Attachment orientations, rejection sensitivity, self-esteem and sexual interest perception were examined. Two cross-sectional studies were conducted using different sexual interest perception measures. Men high in attachment anxiety perceived more sexual interest, but results were mixed for the other individual differences.